Association of patient socioeconomic status with outcomes after palliative treatment for disseminated cancer - Maduka, Richard C.; Canavan, Maureen E.; Walters, Samantha L.; Ermer, Theresa; Zhan, Peter L.; Kaminski, Michael F.; Li, Andrew X.; Pichert, Matthew D.; Salazar, Michelle C.; Prsic, Elizabeth H.; Boffa, Daniel J. (Cancer Medicine, 2024)
Background: Palliative treatment has been associated with improved quality of life and survival for a wide variety of metastatic cancers. However, it is unclear whether the benefits of palliative treatment are uniformly experienced across the US cancer population. We evaluated patterns and outcomes of palliative treatment based on socioeconomic, sociodemographic and treating facility characteristics. Methods: Patients diagnosed between 2008 and 2019 with Stage IV primary cancer of nine organ sites were analyzed in the National Cancer Database. The association between identified variables, and outcomes concerning the administration of palliative treatment were analyzed with multivariable logistic regression and Cox proportional hazard models. Results: Overall 238,995 (23.6%) of Stage IV patients received palliative treatment, which increased over time for all cancers (from 20.7% in 2008 to 25.6% in 2019). Palliative treatment utilization differed significantly by region (West less than Northeast, OR: 0.55 [0.54–0.56], p < 0.001) and insurance payer status (uninsured greater than private insurance, OR: 1.35 [1.32–1.39], p < 0.001). Black race and Hispanic ethnicity were also associated with lower rates of palliative treatment compared to White and non-Hispanics respectively (OR for Blacks: 0.91 [0.90–0.93], p < 0.001 and OR for Hispanics: 0.79 [0.77–0.81] p < 0.001). Conclusions: There are important differences in the utilization of palliative treatment across different populations in the United States. A better understanding of variability in palliative treatment use and outcomes may identify opportunities to improve informed decision making and optimize quality of care at the end-of-life.
CRIS-Team Scopus Importer:2024-05-24
Keywords: cancer education; cancer management; chemotherapy; palliative treatment